THE INFLUENCE OF CLIMATIC CONDITIONS ON THE DYNAMICS OF DENGUE HEMORRHAGIC FEVER: LITERATURE REVIEW - Samal, Rizky Febryan; Adi, Mateus Sakundarno; Nurjazuli, Nurjazuli (Poltekkes Kemenkes Bandung, 2025)
Dengue hemorrhagic fever is a major global health problem influenced by climate change and environmental factors, such as temperature, humidity, wind speed, rainy days, rainfall and sun hours. This study aims to analyze how climate conditions influence the transmission dynamics of dengue hemorrhagic fever. Twenty studies from tropical and subtropical regions were selected for this study using the PRISMA 2020 method, with cross-sectional, cohort, and ecological study designs. These studies were sourced from Google Scholar, ScienceDirect, PubMed, and Garuda. A total of 20,510 publications met the search criteria. After screening for year, full text, and abstract relevance, only 20 journals met the inclusion criteria for this article. This study included articles published between 2019 and 2024 that were officially published and available in full text, as well as non-duplicated articles. The study concluded that climatic conditions affect the transmission dynamics of dengue hemorrhagic fever.